Optimalisasi Pakan dengan Penggunaan Feed Supplement sebagai Upaya Pengembangan Peternakan di Desa Karangtengah, Banjarnegara - Kurniawan, Kuniawan; Puspa, Devi Gibran Purnama; Mukti, Wibowo Arya; Zahra, Novi Kaisa Az; Ramadhani, Athaya Sekar; Handayani, Elis; Nurhida, Dinda; Wirawan, Nandana Rafif; Darmawan, Arif (Jurnal Pusat Inovasi Masyarakat, 2024)
Karangtengah Village in Batur District, Banjarnegara Regency, is an area that has the potential to be developed, especially in the livestock sector. The geographical conditions surrounded by plantations and the socio-economic conditions of the community, most of whom earn a living as farmers and breeders, are supporting factors for the livestock business's development. Development is carried out by introducing feed supplements and their application as additional feed given to livestock to increase farmers' awareness of meeting micronutrient needs and providing information related to the technology of making mineral blocks as animal feed supplements. The method used is Participatory Rural Appraisal (PRA), which involves farmers from the beginning to the end of the program. Activities began with data collection, physical examination of sheep, and education on the importance of feed supplements, especially mineral blocks, which help overcome livestock health problems due to mineral deficiencies. Training on making mineral blocks was conducted theoretically and practically by 12 participants from the Serdang Merdada livestock group and individual farmers. The results showed a significant increase in knowledge, as indicated by a higher post-test score than the pre-test. The "Mineral Block Making Demonstration" Activity Program of IPB 2024 Kuliah Kerja Nyata Tematik (KKNT Inovasi) in Karangtengah Village encourages the adoption of better and sustainable animal husbandry practices. This program provides tangible benefits in improving the welfare of farmers and the quality of livestock products.